Exposure of CD34+ precursors to cytostatic anthraquinone-derivatives induces rapid dendritic cell differentiation: implications for cancer immunotherapy - van de Ven, Rieneke; Reurs, Anneke W.; Wijnands, Pepijn G. J. T. B.; van Wetering, Sandra; Kruisbeek, Ada M.; Hooijberg, Erik; Scheffer, George L.; Scheper, Rik J.; de Gruijl, Tanja D. (Cancer Immunology, Immunotherapy, 2012)
Appropriate activation of dendritic cells (DC) is essential for successful active vaccination and induction of cell-mediated immunity. The scarcity of precursor cells, as well as long culture methods, have hampered wide-scale application of DC vaccines derived from CD34 + precursors, despite their suggested superior efficacy over the more commonly applied monocyte-derived DC (MoDC). Here, employing the CD34 + /CD14 + AML-derived human DC progenitor cell line MUTZ3, we show that cytostatic anthraquinone-derivatives (i.e., the anthracenedione mitoxantrone and the related anthracyclin doxorubicin) induce rapid differentiation of CD34 + DC precursors into functional antigen-presenting cells (APC) in a three-day protocol. The drugs were found to act specifically on CD34 + , and not on CD14 + DC precursors. Importantly, these observations were confirmed for primary CD34 + and CD14 + DC precursors from peripheral blood. Mitoxantrone-generated DC were fully differentiated within three days and after an additional 24 h of maturation, were as capable as standard 9-day differentiated and matured DC to migrate toward the lymph node-homing chemokines CCL19 and CCL21, to induce primary allogeneic T cell proliferation, and to prime functional MART1-specific CD8 + T lymphocytes. Our finding that anthraquinone-derivatives like mitoxantrone support rapid high-efficiency differentiation of DC precursors may have consequences for in vitro production of DC vaccines as well as for novel immunochemotherapy strategies.